Ruxolitinib combined with etanercept induce a rapid response to corticosteroid‐refractory severe acute graft vs host disease after allogeneic stem cell transplantation: Results of a multi‐center prospective study. Issue 9 (6th July 2020) - Zhao, Yanmin; Wu, Hengwei; Shi, Jimin; Luo, Yi; Li, Xiaoqing; Lan, Jianping; Ni, Wanmao; Lu, Ying; Chen, Lieguang; Tan, Yamin; Lai, Xiaoyu; Yu, Jian; et al.
Abstract: About half of patients with severe acute graft vs host disease (aGVHD) show resistance to treatment with first‐line steroids. We enrolled 64 patients with grades III‐IV SR‐aGVHD after allogeneic hematopoietic stem cell transplantation (allo‐SCT), to assess the efficacy and safety of the combination therapy of ruxolitinib and etanercept. The overall response rate was 87.5% (95% CI, 79.7%‐95.3%) at day 28 of the combination treatment, from which 73.4% reached complete response (CR). A marked reduction ≥75% in daily corticosteroid dosing was documented in 75.4% of patients at day 28. Delayed time from aGVHD to ruxolitinib (OR = 4.88, 95% CI, 0.98‐23.56), stages 3‐4 liver aGVHD (OR = 8.57, 95% CI, 0.96‐46.59) and gut Enterobacteriaceae colonization (OR = 12.39, 95% CI, 1.71‐59.77) were related to incomplete response. Grades 3/4 anemia, leukopenia, or thrombocytopenia and CMV‐reactivation were found in 29.7%, 26.6%, 39.1%, and 50.0% of patients, respectively. So, 25 (39.1%) experienced complications of severe infection ≥3 grade, in which pulmonary infections were most frequent (15/64, 23.4%). The 2‐year overall survival (OS) after the combination therapy was 61.2%. The 2‐year incidence of non‐relapse mortality and relapse of the underlying malignancy was 26.7% and 15.7%, respectively. Combined treatment with ruxolitinib and etanercept was very effective and relatively safe for severe aGVHD patients, while the various infection complications deserve more attention. This study was registered at the Chinese Clinical Trial Registry (ChiCTR1900024408).